HIBCH deficiency in a patient with phenotypic characteristics of mitochondrial disorders. Issue 12 (23rd September 2014) - Reuter, Miriam S.; Sass, Jörn Oliver; Leis, Thomas; Köhler, Julia; Mayr, Johannes A.; Feichtinger, René G.; Rauh, Manfred; Schanze, Ina; Bähr, Luzy; Trollmann, Regina; Uebe, Steffen; Ekici, Arif B.; et al.
<x xml:space="preserve">Abstract</x> HIBCH (3‐hydroxyisobutyryl‐CoA hydrolase) deficiency (MIM #250620) is a rare autosomal recessive inborn error of metabolism, leading to a block in the catabolic pathway of the amino acid valine and presumably to accumulation of toxic valine metabolites in mitochondria. Only three families with HIBCH deficiency and biallelic HIBCH mutations have been described. We report on a further patient, first child of healthy consanguineous parents, with severe developmental delay, seizures, hyperintensities of the basal ganglia on magnetic resonance imaging (MRI), progressive brain atrophy, optic nerve atrophy, repeatedly elevated blood lactate, and respiratory chain complexes I, I + III and cytochrome c oxidase deficiencies with borderline depletion of mitochondrial DNA in muscle tissue. Laboratory findings in blood and skeletal muscle were inconsistent and did not allow a definite diagnosis, but supported the hypothesis of mitochondrial dysfunction. Homozygosity mapping and whole‐exome sequencing revealed a homozygous one‐base pair insertion in HIBCH. Deficiency of enzyme activity was confirmed in cultured fibroblasts. Although relatively unspecific, the clinical features were similar to those of the previously reported cases. Given the clinical variability and large number of differential diagnoses, the prevalence of HIBCH deficiency is probably underestimated. Next‐generation sequencing approaches are an effective tool for identifying the underlying genetic basis in patients suspected of mitochondrial disorders. © 2014 Wiley Periodicals, Inc.